A self-aware paradigm for autonomous architectural systems within the Internet of Things. (18th December 2017) - Elsherif, Ahmed; Mandour, Dina; Ali, May A. Malek; Sedky, Mohamed
Abstract: This research explores a newfangled approach for the notion that architecture is no longer concerned with the organization of space and matter, but rather a system of systems with self-organizational behavior and progressively complex programmatic interventions. Such system represents an Internet of Things (IoT) paradigm that has the capacity to self-organize a pre-defined architecture acclimating dynamically to the demands of the environment through a process of self-awareness and re-configurability. This paper is an attempt to develop spaces that bring computation into the physical world by introducing artificial intelligence into building systems so as to communicate, exchange information, and allow right responses and decisions within a sustainable manner. Environments with embedded computational systems and adaptive reconfiguration behavior will be precisely studied. With an intensive focus on smart, self reconfiguring architecture that has embraced kinetic motion as an approach for environmental adaptation and responsiveness. This study addresses the networked organization of sensory systems that incorporate computational platforms in relation to user's desires, where architecture turns into an interactive intermediary between human and computation. Correspondingly, the authors are particularly aiming to propose three conceptual frameworks for delivering a smart system at the architectural scale which is capable of reconfiguring and interacting constantly in real time, precisely focusing on an initial implementation for the first framework utilizing an experimental customized prototype, while the other two frameworks would be subsequently studied through future work. Thus the IoT will foster a rapid development in intelligent systems which would directly introduce an advanced technological leap forward in accommodating a new way of demonstrating human-computer interaction within a novel architectural design approach. Abstract : The figure introduces three diverse approaches for reconfiguring an architectural space –for a smart campus- through the Internet of Things as an autonomous paradigm for anticipating and receiving parameters of particular inputs within a relevant context of students' interaction with university programs.